Effect of the Processing-Induced Morphology on the Mechanical Properties of Biodegradable Extruded Films Based on Poly(lactic acid) (PLA) Blends - Siccardi, Mathilde (2019)
Biodegradable films based on poly(lactic acid) blends were obtained by cast extrusion. Their tensile and fracture behaviorwas investigated and the effect of the processing conditions through the extrusion rolling speed on this behavior was analyzed.In uniaxial tensile tests, all films presented completely ductile behavior exhibiting a defined yield point, strain softeningafter this point and a plateau before fracture. Fracture behavior was determined through quasi-static fracture tests on deeplydouble edge notched tensile specimens. The film obtained at the lowest rolling speed exhibited completely ductile behaviorhence, the Essential Work of Fracture methodology was applied to characterize its fracture. The film processed at intermediaterolling speed, on the other hand, presented ductile fracture or ductile instability depending on the ligament lengthand the film obtained with the highest rolling speed exhibited a transition regime fracture. In order to compare the fracturebehavior of the different films, the J-integral at maximum load Jmax was adopted. Differences in the films fracture behaviorwere correlated to the processing-induced morphology.